PENGARUH BIAYA PRODUKSI DAN BIAYA PEMASARAN TERHADAP VOLUME PENJUALAN - Nilas, Nilas (JIEM : Journal Of International Entrepreneurship And Management, 2022)
This research aims to evaluate the influence of production costs (X1) and marketing expenses (X2) on sales volume (Y). Using a quantitative approach, the study involves 40 employees of the company as randomly selected respondents. Data were collected through questionnaires and analyzed using multiple linear regression. The results indicate that production costs have a positive partial effect on sales volume, suggesting that effective control of production costs can enhance the company's performance. Marketing expenses also have a positive partial effect on sales volume, highlighting that proper allocation of marketing expenses can attract consumers and boost sales. Simultaneously, both production costs and marketing expenses significantly impact sales volume. In conclusion, the efficient utilization of production and marketing costs can lead to an increase in the company's sales volume.